A retrospective study on the trends in surgical aortic valve replacement outcomes in the post‐transcatheter aortic valve replacement era. Issue 3 (22nd May 2022) - Chahine, Johnny; Jedeon, Zeina; Fiocchi, Jacob; Shaffer, Andrew; Knoper, Ryan; John, Ranjit; Yannopoulos, Demetris; Raveendran, Ganesh; Gurevich, Sergey
Abstract: Background and Aims: Transcatheter aortic valve replacement (TAVR) is the mainstay of treatment of inoperable and severe high‐risk aortic stenosis and is noninferior to surgical aortic valve replacement (SAVR) for low‐risk and intermediate‐risk patients as well. We aim to compare the valve size, area, and transaortic mean gradients in SAVR patients before and after the implementation of TAVR since being approved by the Food and Drug Administration  in 2011. Methods: Patients who underwent a bioprosthetic SAVR placement were divided into two groups based on the date of procedure: the early pre‐TAVR implementation group (years 2011–2012) and the contemporary post‐TAVR group (years 2019–2020). The primary endpoint was the mean gradient across the aortic valve within 16 months of surgery. The secondary endpoints included the difference in valve size and various aortic valve echocardiographic variables. Results: One hundred and thirty patients had their valves replaced in the years 2011–2012 and 134 in the years 2019–2020. The early group had a significantly higher mean gradient (median of 13 mmHg [interquartile range,  IQR: 9.3–18] vs. 10 mmHg [IQR: 7.5–13.1], p  = 0.001) and a smaller median effective orifice area index (0.8 cm 2 /m 2 [IQR: 0.6–1] vs. 1.1 cm 2 /m 2 [IQR: 0.8–1.3], p  < 0.001). The median valve size was significantly smaller in the early group (median of 21 mm [IQR: 21–23] vs. 23 mm [IQR: 22.5–25], p  < 0.001). Conclusion: In the contemporary era, surgical patients receive larger valves which translates into lower mean gradients, larger valve area, and lower rates of patient‐prosthesis mismatch than in previous years before the routine introduction of TAVR.